(untitled) (Journal of actual problems of jurisprudence, 2016)
In the article the authors discusses about a problem of information security and copyright protection in the Internet.Development of information technologies makes improve the legislative base. Boundless information space use information technology and the Internet, brings together people from different countries into one global community. Тhe process complicates the protection of the rights of authors.